2018
DOI: 10.1155/2018/9829856
|View full text |Cite
|
Sign up to set email alerts
|

Postauricular Melanocytic Neuroectodermal Tumor of Infancy: A Rare Site of a Rare Tumor—MNTI as a Postauricular Mass with Literature Review

Abstract: Melanocytic neuroectodermal tumor of infancy (MNTI) is a rare osteolytic neoplasm of neural crest cell origin. There are less than 500 documented cases, most frequently affecting the maxilla of infants less than 1 year old. We present a unique case of a two-month-old male with a progressive postauricular mass since birth, confirmed to be a MNTI. The lesion required three resections over the course of five months, with rapid recurrence ultimately requiring a craniectomy, highlighting the difficulty in treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…Other reported sites of origin include the central nervous system, mediastinum, uterus, epididymis, ovary, testes, upper arm, thigh, post auricular subcutaneous tissue and skin [3,[17][18][19][20][21]. Malignant change can occur and has been reported to range from 1.9% -6.5% of cases.…”
Section: Discussionmentioning
confidence: 99%